(untitled) (Journal of Fiber Bioengineering and Informatics, 2013)
An abaya is a traditional Muslim woman's outer garment. It is black and worn on a day-to-day basis when women are outside their homes. The abaya absorbs most of the heat from sunlight in a hot climate as it is black, making the wearer very uncomfortable. In order to reduce absorption of heat in an abaya and to make the wearer more comfortable, it is proposed that a treatment with a solar energy reflector could enable the wearer to perspire less; thus allowing them to feel cooler. This paper investigates the thermal comfort properties of plain-woven fabrics dyed in black and treated chemically to reflect a proportion of sunlight's energy. The fabrics were made from 100% wool and two polyester/wool blends. The testing results showed that the fabrics that had received the reflective treatment possessed marginally improved thermal comfort properties as compared to fabrics without the treatment.